Kesetaraan Akses Digital - Wahida Suddin; Muh Akbar; Nur Riswandi Marsuki (Institut Nalanda, 2024)
The goal of equal digital access is to create a digitally inclusive society, where everyone has the same opportunity to access, understand and utilize digital technology in their daily lives. Digital access equality functions are critical in an increasingly digitally connected society, as they help create a more inclusive, equitable and sustainable environment for all individuals.